Analysis of photoaging characteristics of Chinese traditional pigments and dyes in different environments based on color difference principle. Issue 6 (29th May 2021) - Zhao, Zining; Zhang, Peng; Liu, Xianming; Lei, Xiaohua; Luo, Yun
Abstract: Photocatalytic oxidation is one of the main factors leading to the aging damage of Chinese traditional dyes and pigments. In this study, in order to analyze the photoaging characteristics of traditional dyes and pigments commonly used in Chinese cultural relics in different environments, we used traditional Chinese painting pigments to make colored paper samples, and used traditional dye extraction and dyeing technology to make colored silk samples. By setting up nitrogen and atmospheric chamber and using LED, tungsten halogen lamp, metal halide lamp and fluorescent lamp as light sources, an accelerated photoaging contrast test on 16 kinds of dyes and pigments was carried out, and then the color difference of different samples in different light environment and atmosphere environment was obtained. Through systematic analysis, the results show that the type of light source and the gas environment will affect the photoaging rate of the samples. The nitrogen environment can significantly reduce the degree and speed of photoaging, especially for organic dyes and pigments.